Virtual Sound Localization by Blind People - DUNAI, Larisa; LENGUA, Ismael; PERIS-FAJARNÉS, Guillermo; BRUSOLA, Fernando (Archives of Acoustics, 2015)
The paper demonstrates that blind people localize sounds more accurately than sighted people by using monaural and/or binaural cues. In the experiment, blind people participated in two tests; the first one took place in the laboratory and the second one in the real environment under different noise conditions. A simple click sound was employed and processed with non-individual head related transfer functions. The sounds were delivered by a system with a maximum azimuth of 32^° to the left side and 32^° to the right side of the participant’s head at a distance ranging from 0.3 m up to 5 m. The present paper describes the experimental methods and results of virtual sound localization by blind people through the use of a simple electronic travel aid based on an infrared laser pulse and the time of flight distance measurement principle. The lack of vision is often compensated by other perceptual abilities, such as the tactile or hearing ability. The results show that blind people easily perceive and localize binaural sounds and assimilate them with sounds from the environment.